Behavior of Mortality According to Necropsy in Internal Medicine and Geriatrics Services of Cienfuegos - Ana Laura Navarro Baldellot; Laidamy Rodríguez Amador; Roine Alberto Pena Olivera; Héctor Javier Cruz de los Santos; Lisanka Fumero Roldán; Samuel Sánchez Sánchez (Universidad de las Ciencias Médicas de Cienfuegos, 2021)
Background: mortality is one of the main indicators of quality in hospital care and management because it is considered a measure of the effectiveness of health intervention Objective: to determine the causes of mortality according to autopsy in the Internal Medicine and Geriatrics Services of Cienfuegos in the period 2017-2019. Methods: a descriptive-retrospective case series was carried out, of the 730 deceased patients who underwent autopsy between January 2017 and December 2019. Clinical and epidemiological variables were used. The information obtained was stored and processed in the statistical package SPSS version 21.0 for Windows. Measures of central tendency were applied to the quantitative variables, the qualitative ones were measured in index, in absolute and relative frequencies, depending on the distribution of each one of them. Results: the mean age was 75 years. Male sex predominated (57.8 %). The most represented age group was 70-79 years (28.9 %). The highest number of autopsies was performed in 2017 (37.7 %). The mean hospital stay was 8 days. The stay of less than three days predominated in the series (39.9 %). The most commonly reported causes of direct death were bronchopneumonia / pneumonia (61.3 %), then cardioangiosclerosis-pulmonary edema (13.1 %) and end-stage lung neoplasia (5.3 %). Conclusions: the most declared causes of direct death were bronchopneumonia and pneumonia. There was an adequate clinical-pathological correlation in these groups. The best levels of clinicopathological agreement were found in diseases of the central nervous system, tumors, and respiratory diseases. There was a worse correlation between digestive diseases, some infections and circulatory pathologies.